Типы садков для лабораторного содержания пауков - Пичка, В.Е. (Вестник зоологии, 1974)
An individual maintenance of each spider zooid is one of the conditions for successful laboratory cultivation of the spiders. A study of reproduction and development of Linyphia triangularis C 1. and Agelena labyrinthica (C 1.) permits recommending glass test-tubes 6 cm long and 1 cm diameter as breeding chambers for young spiders; the special breeding chambers (Figs. 2, 3) are suggested for the elder nymphs and imago. Diapausing stages of the spiders are well preserved in the chambers suggested by Zvolfer at temperature +HP C and air humidity 78%.